2006
DOI: 10.1007/s00259-005-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Loss of neuronal integrity: a cause of hypometabolism in patients with traumatic brain injury without MRI abnormality in the chronic stage

Abstract: These results indicate that there are metabolic abnormalities in TBI patients with some symptoms after brain injury but without abnormalities on MRI. Some of the hypometabolic lesions showed low BP, indicating a loss of neuronal integrity. Thus, FMZ PET may have potential to distinguish hypometabolism caused by neuronal loss from that caused by other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…A possible explanation for these findings is that the restorative capacity of memantine may particularly affect attention, executive function, and working memory by increasing cerebral glucose metabolism in the frontal and the parietal cortices. Cerebral hypometabolism associated with cognitive impairment after TBI has been demonstrated diffuse or focal lesions in the frontal, parietal, temporal, and occipital cortices [26,27]. There are a few preliminary studies [22,28] demonstrating a enhancing effect of memantine on the frontal cerebral metabolism in schizophrenia [22] and alcohol-induced dementia [28], but not much is known about the underlying mechanism of memantine's effect on cognition and cerebral metabolism in TBI.…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation for these findings is that the restorative capacity of memantine may particularly affect attention, executive function, and working memory by increasing cerebral glucose metabolism in the frontal and the parietal cortices. Cerebral hypometabolism associated with cognitive impairment after TBI has been demonstrated diffuse or focal lesions in the frontal, parietal, temporal, and occipital cortices [26,27]. There are a few preliminary studies [22,28] demonstrating a enhancing effect of memantine on the frontal cerebral metabolism in schizophrenia [22] and alcohol-induced dementia [28], but not much is known about the underlying mechanism of memantine's effect on cognition and cerebral metabolism in TBI.…”
Section: Discussionmentioning
confidence: 97%
“…225 One study showed decreased [ 11 C]flumazenil binding only if there was low CMRO 2 , suggesting that decreased cortical metabolism is in some cases associated with neuronal loss. 226 A study using [ 11 C]MP4A, a tracer for cortical acetylcholinesterase activity, showed decreased cholinergic function in parietal and cingulate cortex; this finding may be relevant to the use of acetylcholinesterase inhibitors to treat the cognitive symptoms of chronic TBI. 227 Two recent reports of studies use the radiopharmaceutical [ 11 C]PK11195, a marker for neuroinflammation that reflects microglial activation and increased macrophages.…”
Section: Chronic Tbimentioning
confidence: 96%
“…FDG-PET studies indicate significant metabolic abnormalities that persist for weeks to months following TBI [53], often observed in areas of the brain which appear structurally normal on conventional MRI and CT [54]. A pattern of diffuse cerebral hypometabolism has been found in patients with TBI and has been associated with poor neurocognitive outcome [55][56][57].…”
Section: Positron Emission Tomographymentioning
confidence: 98%